2022
DOI: 10.3847/2041-8213/ac9a47
|View full text |Cite
|
Sign up to set email alerts
|

A Transient “Changing-look” Active Galactic Nucleus Resolved on Month Timescales from First-year Sloan Digital Sky Survey V Data

Abstract: We report the discovery of a new “changing-look” active galactic nucleus (CLAGN) event, in the quasar SDSS J162829.17+432948.5 at z = 0.2603, identified through repeat spectroscopy from the fifth Sloan Digital Sky Survey (SDSS-V). Optical photometry taken during 2020–2021 shows a dramatic dimming of Δg ≈ 1 mag, followed by a rapid recovery on a timescale of several months, with the ≲2 month period of rebrightening captured in new SDSS-V and Las Cumbres Observatory spectroscopy. This is one of the fastest CLAGN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…Over 100 CL AGNs have been discovered based on their Balmer-line profile transitions (MacLeod et al 2016;Gezari et al 2017;Sheng et al 2017;Frederick et al 2019;Green et al 2022;Hon et al 2022;Zeltyn et al 2022;Chen et al 2023;Yang et al 2023), and dozens of CL AGNs have also been identified based on transitions in Mg II, C III], and C IV (Guo et al 2019(Guo et al , 2020Ross et al 2020). However, the nature and frequency of CL AGNs are still not well understood, and many questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Over 100 CL AGNs have been discovered based on their Balmer-line profile transitions (MacLeod et al 2016;Gezari et al 2017;Sheng et al 2017;Frederick et al 2019;Green et al 2022;Hon et al 2022;Zeltyn et al 2022;Chen et al 2023;Yang et al 2023), and dozens of CL AGNs have also been identified based on transitions in Mg II, C III], and C IV (Guo et al 2019(Guo et al , 2020Ross et al 2020). However, the nature and frequency of CL AGNs are still not well understood, and many questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…However, we know that at least some CL transitions occur on much shorter timescales (e.g. Gezari et al 2017;Trakhtenbrot et al 2019;Zeltyn et al 2022) which we would miss in cases where a source transitions twice (e.g. off and then on again) within ≈300 days.…”
Section: Time-scales Of CL Eventsmentioning
confidence: 96%
“…While constant reddening should not affect the variability amplitudes, it does affect the relative luminosities between wavelength bands, and consequently our model fit results. In addition, a hypervariable quasar with dramatically variable reddening has recently been discovered from SDSS-V (Zeltyn et al 2022). Variable reddening would alter the variability amplitude and the likely reprocessing geometry of the hypervariable quasar.…”
Section: Host-galaxy Contributions and Reddeningmentioning
confidence: 99%